2015
DOI: 10.1186/s40164-015-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of erythropoiesis-stimulating agents with ruxolitinib in patients with myelofibrosis in COMFORT-II: an open-label, phase 3 study assessing efficacy and safety of ruxolitinib versus best available therapy in the treatment of myelofibrosis

Abstract: BackgroundAnemia is considered a negative prognostic risk factor for survival in patients with myelofibrosis. Most patients with myelofibrosis are anemic, and 35–54 % present with anemia at diagnosis. Ruxolitinib, a potent inhibitor of Janus kinase (JAK) 1 and JAK2, was associated with an overall survival benefit and improvements in splenomegaly and patient-reported outcomes in patients with myelofibrosis in the two phase 3 COMFORT studies. Consistent with the ruxolitinib mechanism of action, anemia was a freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…A lower need for transfusions was recorded in patients responding to ruxolitinib, together with a reduction of symptoms. An association of ruxolitinib to erythropoietin may be useful in this phase, as suggested in another report [15]; our experience shows that some patients become sensitive to erythropoietin following ruxolitinib. As regards the hematologic status, we modulated the dose of therapy according to the presence of anemia and platelets number; patients who received less than 40 mg/day of ruxolitinib had a significantly shorter duration of response even if the response rate was similar in both patients groups.…”
Section: Discussionmentioning
confidence: 73%
“…A lower need for transfusions was recorded in patients responding to ruxolitinib, together with a reduction of symptoms. An association of ruxolitinib to erythropoietin may be useful in this phase, as suggested in another report [15]; our experience shows that some patients become sensitive to erythropoietin following ruxolitinib. As regards the hematologic status, we modulated the dose of therapy according to the presence of anemia and platelets number; patients who received less than 40 mg/day of ruxolitinib had a significantly shorter duration of response even if the response rate was similar in both patients groups.…”
Section: Discussionmentioning
confidence: 73%
“…Although findings are preliminary, concomitant administration of erythropoiesisstimulating agents was well tolerated and did not have a negative impact on the efficacy of ruxolitinib, as was seen in COMFORT-II. 14 The rates of infections in JUMP were low and the infections were primarily grade 1/2; no new or unexpected infections were observed. Additionally, no cases of progressive multifocal leukoencephalopathy were reported.…”
mentioning
confidence: 86%
“…Moreover, ruxolitinib has not been reported to improve the haemoglobin (Hb) level in patients already anaemic at treatment start (Harrison et al , ; Verstovsek et al , ). The use of erythropoiesis‐stimulating agents (ESAs) was discouraged in the COMFORT I study, however some responses to ESAs were seen in 13 patients from the COMFORT II study and reported in a post hoc analysis (McMullin et al , ).…”
mentioning
confidence: 99%